Taekwondo Sport Development in Sukoharjo District - Luthfi Ramdhansyah; Sugiyanto Sugiyanto; Sapta Kunta Purnama (Budapest International Research and Critics University, 2022)
Taekwondo is a martial art that requires mental toughness and high self-confidence. The purpose of this study was to determine: (1) Taekwondo organizational system in Sukoharjo Regency, (2) Taekwondo sports management management in Sukoharjo Regency, (3) Taekwondo athlete development in Sukoharjo Regency. The research method used is descriptive research with a qualitative approach. Sources of data in this study came from taekwondo administrators in Sukoharjo district: taekwondo coaches, athletes, and taekwondo members in Sukoharjo district. Data collection techniques using interviews, observations, and documents. The technique of taking research subjects was purposive sampling with a sample of six people. The results of this study are that the organizational system for coaching taekwondo athletes that has been going on from 1993 until now has produced many achievements, this is because the taekwondo athlete coaching system in Sukoharjo Regency has been running according to the predetermined household budget. All members of the taekwondo organization have carried out their duties according to their respective sections.